First-Principles Simulation of the Interaction Between DNA Nucleotides and One-Dimensional Carbon Chain in Electrical Based Sequencing - Zeina Salman; Jin-Woo Kim; Steve Tung (IEEE Open Journal of Nanotechnology)
Electrical DNA sequencing has attracted significant attention in recent years due to its simplified sequencing protocol, compact sequencing system, and relatively low sequencing cost. In the design and fabrication of the sequencing device, carbon-based nanomaterials such as graphene have been explored as a promising sensing material that provides an excellent combination of spatial resolution and base specificity. Using first-principles simulation, we determined the effect on the electrical conductivity of a one-dimensional carbon chain due to the presence of four DNA bases. The simulation results indicate that the interaction between the carbon chain and different DNA bases leads to different levels of conductivity change in the carbon chain. Quantitatively, base A is the most difficult base to detect due to its relatively small current change. Furthermore, the results also show that the relative orientation of the bases with respect to the carbon chain can affect the induced current change in the chain. This information can be used to optimize the structural design of future sequencing devices. Collectively, the first-principles simulation results suggest the integration of a one-dimensional carbon chain with supporting nanofluidic designs can provide a viable approach towards the development of a compact, robust, and high-resolution DNA sequencing system.